The scope of the common good in Peruvian constitutional jurisprudence: An examination of compatibility between John Finnis’s contributions and the Peruvian Constitutional Court - Begazo Cáceres, Alonso Ramiro (2024)
This investigation seeks to examine whether the idea of ​​common good developed in the Peruvian Constitutional Court jurisprudence is compatible with the notion of “common good” developed by John Finnis. As a starting point, through an axiological review, we will establish what Finnis's concept of the common good is, who, based on a rereading of the Aristotelian-Thomistic postulates, offers a broad vision of the matter with clear specifications in practical behavior. political and legal. Then, we will focus on a dogmatic review of the concept of political common good and its most relevant relationships based on the scope of Peruvian constitutional jurisprudence; finally, evaluating whether it is possible to establish the compatibility of these two notions, with the purpose of clarifying and expanding the jurisprudential postulates from the criteria developed by the author to be discussed.